Inflammatory Bowel disease promote oral cancer and pharyngeal cancer: new evidence of Mendelian randomization. (1st February 2022) - Chen, Gui; Xie, Junyang; Liang, Tianhao; Wang, Yiyan; Liao, Wenjing; Song, Lijuan; Zhang, Xiaowen
Abstract: Background: Evidence from observational studies shows that inflammatory bowel disease (IBD) [comprising ulcerative colitis (UC) and Crohn's disease (CD)] is a risk factor to Oral cavity and pharyngeal cancer (OC&PC) [comprising Oral cavity cancer (OCC) and Oropharyngeal cancer (OPC)], but it is unclear whether these diseases have potential causality. Objectives: We aimed to explore the causal relationship between IBD and OC&PC. Materials and methods: A mendelian randomized (MR) study was performed to estimate the causal relationship between IBD and OC&PC. Results: The potential causal relationship was statistically significant between IBD and OCC (OR = 1.14, 95% confidence interval (CI): 1.02–1.27, p  = .02), UC and OCC (OR = 1.13, 95% CI: 1.01–1.27, p  = .03), respectively. There was a universal null effect of IBD on OC&PC (IBD: OR = 1.01, 95%CI: 0.93–1.10, p  = .74; UC: OR = 1.00, 95%CI: 0.92–1.10, p  = .94; CD: OR = 1.02, 95%CI: 0.94–1.09, p  = .69), and IBD on OPC (IBD: OR = 0.93, 95%CI: 0.81–1.06, p  = 0.26; UC: OR = 0.90, 95%CI: 0.79–1.03, p  = .12; CD: OR = 1.04, 95%CI: 0.94–1.15, p  = .44). Conclusions and significance: MR analyses support new evidence indicating there may be a positive causal effect of IBD (including UC) on OCC. Further investigation of the potential biological mechanisms is necessary.